2015
DOI: 10.1242/jeb.122622
|View full text |Cite
|
Sign up to set email alerts
|

Pitch perfect: how fruit flies control their body pitch angle

Abstract: Flapping insect flight is a complex and beautiful phenomenon that relies on fast, active control mechanisms to counter aerodynamic instability. To directly investigate how freely flying Drosophila melanogaster control their body pitch angle against such instability, we perturbed them using impulsive mechanical torques and filmed their corrective maneuvers with high-speed video. Combining experimental observations and numerical simulation, we found that flies correct for pitch deflections of up to 40 deg in 29±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(86 citation statements)
references
References 76 publications
6
79
1
Order By: Relevance
“…In contrast, a study by Whitehead et al (2015) showed that D. melanogaster can initiate a pitch stabilisation locomotion (by wing-stroke modulation) in only 10±2 ms, significantly faster than the results in the present study. This is also likely due to the different roles of the abdomen addressed earlier, as well as the fundamental differences in the responses of insects in free-flight versus tethered conditions (as the body orientation of the insect is not physically altered under tethered conditions).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, a study by Whitehead et al (2015) showed that D. melanogaster can initiate a pitch stabilisation locomotion (by wing-stroke modulation) in only 10±2 ms, significantly faster than the results in the present study. This is also likely due to the different roles of the abdomen addressed earlier, as well as the fundamental differences in the responses of insects in free-flight versus tethered conditions (as the body orientation of the insect is not physically altered under tethered conditions).…”
Section: Discussioncontrasting
confidence: 99%
“…increasing the stroke amplitude and changing the mean stroke angle), resulting in the forward shift of the aerodynamic center. Similar result was given by Whitehead et al [14] For lateral motion, the stroke amplitude also played an important role in controlling roll perturbations [15]. Furthermore, Ristroph and others indicated that the wing pitch angle modulations contribute to roll and yaw corrective torque in fruit flies [11],[16],[17].…”
Section: Introductionsupporting
confidence: 74%
“…Several researches on the fruitflies pitch motion showed that the generation of the pitch moment is ascribed to the shift of mean stroke angle [12],[14]. It’s clear that the shift of mean stroke angle leads to the change of moment arm of the lift to COM and varies the pitch moment.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the fly seems to be measuring the body's angular velocity and its integral, the total angular displacement, to determine the appropriate change in the wing-stroke parameters (Fig. 1) [9,11,12]. Remarkably, flies accomplish this feat of stabilization using a relatively sparse motor system, with only 12 steering muscles to modulate the kinematics of each wing.…”
Section: Discussion-our Approachmentioning
confidence: 99%